2014
DOI: 10.1084/jem.20132486
|View full text |Cite
|
Sign up to set email alerts
|

The linear ubiquitin assembly complex (LUBAC) is essential for NLRP3 inflammasome activation

Abstract: Independent of its known role in NF-κB transcription, the HOIL-1L containing LUBAC is required for assembly and activation of the NLRP3 inflammasome via linear ubiquitination of ASC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
187
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(203 citation statements)
references
References 60 publications
(156 reference statements)
9
187
2
5
Order By: Relevance
“…This raises the possibility of specific host protein DAMPs that are homologous with bacterial NAIP ligands, or that certain DAMPs or tissue/cellular stresses activate posttranslational mechanisms, causing activation of NLRC4. Recent work from our group and others has identified ubiquitin posttranslational modification of NLRP3 inflammasome components as a key integrator of diverse DAMP signals (35)(36)(37)(38). Interestingly, ubiquitination has also been suggested to regulate the activation of NLRC4 in a model of caspase-8-dependent cell death (39).…”
Section: Discussionmentioning
confidence: 98%
“…This raises the possibility of specific host protein DAMPs that are homologous with bacterial NAIP ligands, or that certain DAMPs or tissue/cellular stresses activate posttranslational mechanisms, causing activation of NLRC4. Recent work from our group and others has identified ubiquitin posttranslational modification of NLRP3 inflammasome components as a key integrator of diverse DAMP signals (35)(36)(37)(38). Interestingly, ubiquitination has also been suggested to regulate the activation of NLRC4 in a model of caspase-8-dependent cell death (39).…”
Section: Discussionmentioning
confidence: 98%
“…111 Recently, HOIL-1L, a component of linear ubiquitination assembly complex (LUBAC), was found to be an essential activator of NLRP3/ASC inflammasome assembly through linear ubiquitination of ASC, a novel LUBAC substrate. 112 Additionally, the direct binding of NLRP3 to the mitochondrial lipid cardiolipin is important for NLRP3 inflammasome activation in response to both ROSdependent and -independent activators. 73 Recent studies showed that DHX33, a member of the DExD/ H-box helicase family, plays a role in activation of the NLRP3 inflammasome through interaction with NLRP3.…”
Section: Adaptors/molecules Involved In Activation Of the Nlrp3 Inflamentioning
confidence: 99%
“…S4 B and C). OTULIN cleaves Met1-linked linear polyubiquitin chains from target substrates, such as NEMO (IKKγ), RIPK1, ASC, and TNFR1 to restrict signaling activation and propagation (7,14,15). To investigate the effect of OTULIN mutations on its deubiquitinase function, we cotransfected WT and mutant OTULIN plasmids into HEK293 cells along with plasmids encoding the LUBAC subunits, mono specific-ubiquitin plasmid, and each of the OTULIN substrates NEMO (Fig.…”
Section: Significancementioning
confidence: 99%